2021
DOI: 10.1016/j.ygyno.2020.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a nationwide Dutch guideline to detect Lynch syndrome in patients with endometrial cancer

Abstract: syndrome screening in endometrial cancer can be improved.• Gynaecologists ought to be aware of Lynch syndrome screening in endometrial cancer and might require additional training.• Quality assurance protocols should be implemented to ensure adherence to Lynch syndrome screening in endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
4
8
0
1
Order By: Relevance
“…We identified 57 articles analyzing MLH1 promoter methylation [ 19 , 26 , 32 , 33 , 34 , 36 , 40 , 42 , 46 , 47 , 52 , 55 , 57 , 58 , 59 , 69 , 71 , 75 , 79 , 81 , 82 , 83 , 84 , 85 , 86 , 90 , 91 , 94 , 95 , 96 , 99 , 100 , 112 , 113 , 116 , 122 , 124 , 125 , 127 , 128 , 129 , 136 , 137 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ,…”
Section: Resultsunclassified
“…We identified 57 articles analyzing MLH1 promoter methylation [ 19 , 26 , 32 , 33 , 34 , 36 , 40 , 42 , 46 , 47 , 52 , 55 , 57 , 58 , 59 , 69 , 71 , 75 , 79 , 81 , 82 , 83 , 84 , 85 , 86 , 90 , 91 , 94 , 95 , 96 , 99 , 100 , 112 , 113 , 116 , 122 , 124 , 125 , 127 , 128 , 129 , 136 , 137 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ,…”
Section: Resultsunclassified
“…5,10 There is evidence of significant drop-off between finding an abnormal IHC result and completion of genetic testing. 10,11 A recent countrywide initiative in Canada found that despite universal tumor testing, LS was underdiagnosed. 12 Mutations in cancer susceptibility genes (CSGs) other than those associated with LS are thought to play a smaller role in EC risk.…”
Section: Introductionmentioning
confidence: 99%
“…In a study from the Netherlands, Tjalsma et al showed that of 15 patients with tumor testing suggestive of LS, three (20%) were not informed of the tumor testing results and were not referred for germline genetic testing. Of the remaining 12 patients referred for genetic counseling, only nine completed testing leaving only 9/15 (60%) patients with likely LS having completed genetic testing [8]. Lee et al describe that at their institution (NY, US), 10/583 (1.7%) patients with EC had germline genetic testing confirming the diagnosis of LS.…”
Section: Discussionmentioning
confidence: 99%
“…A large, multi-institution study that prospectively tested newly diagnosed EC patients with tumor and germline testing found that the most common causes of LS in EC were PMS2 and MSH6 PVs and identified numerous challenges with IHC screening that ultimately could have resulted in missed diagnoses of LS [2]. It is important to note that even in those instances in which tumor screening identifies possible LS, the diagnosis is not confirmed until germline genetic testing is completed, with several studies demonstrating a significant drop off between an abnormal IHC result and completion of genetic testing [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%